IMPLEMENTASI GOOD CORPORATE GOVERNANCE SEBAGAI UPAYA MEMINIMALKAN EKSPROPRIASI DALAM MENINGKATKAN KINERJA PERUSAHAAN - Dito Rinaldo (Faculty of Economic and Business, 2012)
The aim of this research is to analyze does good corporate governance mechanism had a good function in order to solve the agents problem in Indonesia such as the ekspropriation to minority share holders through panel data regression. The result of this research is institutional and managerial ownership had a positive influence to MLO but not to NPM. Meanwhile, the institutional ownership had a negative influence to PP, this result has a justification that there had been an expropriation in the company. The managerial ownership variable had a positive influence to PP, this result shown that the debt establishment had pushed the company to incrase the income for paying the fixed cost such as interest. DOI: 10.15408/etk.v11i2.1889